Activation of TMEM16E scramblase induces ligand independent growth factor receptor signaling and macropinocytosis for membrane repair - Jung-Eun Kim; Woori Ko; Siwoo Jin; Jin-Nyeong Woo; Yuna Jung; Inah Bae; Han-Kyoung Choe; Daeha Seo; Bertil Hille; Byung-Chang Suh (Communications Biology)
Abstract The calcium-dependent phospholipid scramblase TMEM16E mediates ion transport and lipid translocation across the plasma membrane. TMEM16E also contributes to protection of membrane structure by facilitating cellular repair signaling. Our research reveals that TMEM16E activation promotes macropinocytosis, essential for maintaining plasma membrane integrity. This scramblase externalizes phosphatidylserine, typically linked to resting growth factor receptors. We demonstrate that TMEM16E can interact with and signal through growth factor receptors, including epidermal growth factor receptor, even without ligands. This interaction stimulates downstream phosphoinositide 3-kinase and facilitates macropinocytosis and internalization of annexin V bound to the membrane, a process sensitive to amiloride inhibition. Although TMEM16E is internalized during this process, it returns to the plasma membrane. TMEM16E- driven macropinocytosis is proposed to restore membrane integrity after perturbation, potentially explaining pathologies in conditions like muscular dystrophies, where TMEM16E functionality is compromised, highlighting its critical role in muscle cell survival.